Analysis of Moringa Leaf Nanoemulgel (Moringa Oleifera L.) and Aloe Vera as A Moisturizer for Male Rabbits in New Zealand - Ariyanti Ariyanti; Eni Masruriati; Dwi Setyowati; Filza Mazaya Nurulita (GLOBAL HEALTH SCIENCE GROUP, 2023)
Moisturizing lotion is an emollient group that contains more water which is useful for increasing skin hydration. One of the active ingredients in the moisturizing lotion is the antioxidant compounds found in Moringa oleifera L. and aloe vera leaves. Moringa leaves contain flavonoids such as quercetin, which have strong antioxidant activity that can neutralize free radicals. Aloe vera contains vitamins A, B, C, E, calcium, amino acids, enzymes and polysaccharides which are useful as moisturizing agents. The formulation of Moringa leaf extract and aloe vera was made in the form of nanoemulgel lotion as a skin moisturizer, before being formulated into a lotion preparation, a phytochemical screening was carried out to determine the content of the extract compounds. This study aims to determine the effect of using nanoemulgel lotion of moringa leaf extract and aloe vera on skin moisture. The formulation of nanoemulgel lotion of moringa leaf extract and aloe vera uses different concentrations of active substances of 3% (F1), 6% (F2) and 9% (F3). The physical evaluation carried out included organoleptic tests, homogeneity, pH, spreadability, viscosity and skin moisture. The results showed that all formulations with concentrations of 3%, 6% and 9% met the requirements for the evaluation test for nanoemulgel lotion for skin moisturizing. The higher the concentration of the active substance, the greater the spreadability and viscosity value obtained, no effect on pH. Nanoemulgel lotion preparations of moreinga leaf extract and aloe vera with a concentration of 9% (F3) have high ability as skin moisturizers.